2016
DOI: 10.1519/jsc.0000000000001083
|View full text |Cite
|
Sign up to set email alerts
|

Lower-Body Torque and Power Declines Across Six Decades in Three Hundred Fifty-Seven Men and Women

Abstract: This study presents age-specific and gender-specific patterns and normative values for lower-body isokinetic performance in 195 women and 162 men, 18-80 years of age, using data collected from 1991 to 2004. Peak torque (PT) and average power (AP) during knee extension (KE), knee flexion (KF), ankle plantar flexion, and dorsiflexion (DF) at 1.05, 3.14, and 5.24 rad · s(-1) were compared by decade. Knee extension and KF at all speeds showed a significant main effect by age group (G). Men's KEPT and KEAP at 60 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 69 publications
3
11
0
Order By: Relevance
“…Moreover, except for maximal gait speed, all other functional outcomes were able to differentiate between the groups, including middle-aged and older adults, suggesting that a reduction in functional capacity may already occur previous to older age, even in apparently healthy individuals. This notion is in line with several impairments already observed during the transition from middle to older age, such as reductions in muscle mass, strength, and power [13,14], which are commonly associated with functional capacity and found to be predictors of incident disability. On the bright side, however, our results demonstrate that it is possible to build a stronger foundation in the younger individuals so that they can better deal with age-related impairments at the same time that it is possible to mitigate and even revert already installed mobility-disability in at-risk populations.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Moreover, except for maximal gait speed, all other functional outcomes were able to differentiate between the groups, including middle-aged and older adults, suggesting that a reduction in functional capacity may already occur previous to older age, even in apparently healthy individuals. This notion is in line with several impairments already observed during the transition from middle to older age, such as reductions in muscle mass, strength, and power [13,14], which are commonly associated with functional capacity and found to be predictors of incident disability. On the bright side, however, our results demonstrate that it is possible to build a stronger foundation in the younger individuals so that they can better deal with age-related impairments at the same time that it is possible to mitigate and even revert already installed mobility-disability in at-risk populations.…”
Section: Discussionsupporting
confidence: 88%
“…This considerable muscle power loss during the aging process is worrisome because power is associated with and is an important predictor of functional performance in elderly people [9][10][11][12]. It should be noted, however, that the loss of lower limb muscle mass, strength, and power seems to begin as early as the fourth decade and, therefore, it is important that preventive measures be implemented as soon as possible and not just later in life [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…These observations highlight an interesting and potentially challenging disconnect between a common clinical criterion, limb symmetry, used to measure improvement from rehabilitation after ACLR and the actual functional status of the individual. Whereas the potential limitations of symmetry as a measure have been described, our findings further the understanding that comparing unilateral knee-extension strength and quadriceps activation with preinjury levels, 38 population-based norms, 39 or patient-centered cutoff scores 15,40 may add value to the LSI. Restoring limb symmetry for knee-extension strength and quadriceps activation, coupled with a return to normal involved-limb quadriceps function, may promote an optimal outcome for individuals after ACLR.…”
Section: Discussionmentioning
confidence: 55%
“…Aging is associated with impairment of the neuromuscular system, including muscle atrophy (muscle mass decreases at a rate of 1% to 2% per year above the age of 50; von Haehling et al, 2010) and decreases in muscle strength (3% after the age of 60; von Haehling et al, 2010). Furthermore, skeletal muscle power declines at a faster rate than muscle strength during aging (Leyva et al, 2016;Reid & Balachandran, 2012), and it has been shown to be more important than muscle strength in the ability to perform daily activities (Bassey et al, 1992). As a consequence, even with healthy aging (in the absence of disease), aging is associated with an age-related physical function decline that is related with increased risk of falling (Moreira et al, 2018), disability (Evans et al, 2010) and loss of independence (Brady et al, 2014).…”
Section: Introductionmentioning
confidence: 99%